Portable Electronic Nose for Discrimination of Indonesian Robusta Coffee Aroma with Varied Roasting Temperature Correlated with Gas Chromatography Mass Spectrometry - Yesiana Arimurti; Kuwat Triyana; Sri Anggrahini (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2019)
The quality of coffee is strongly affected by its aroma, so that instrument for aroma testing is necessary especially for quality control. In this research, coffee aroma was tested using electronic nose and then correlated to gas chromatography-mass spectrometry (GC-MS). The green beans of robusta coffee (coffee canephora var.robusta) originated from Sumatra was used as a testing sample. The roasting temperature was varied to be 180 °C, 195 °C, and 210 °C, while the roasting time was set to be constant at 20 minutes. After the roasting process, the coffee beans were grounded using a coffee grinder. The feature of the response signal for each gas sensors of the electronic nose to ground coffee aroma, was extracted using two methods; i.e. gradient multiplied by signal peak and average value. The principle component analysis (PCA) was applied to discriminate the aroma of ground coffee with varied roasting temperature. The scoreplot of PCA analysis shows a clear discrimination of each coffee aroma, produced by different roasting temperature. From the GCMS analysis, it is clearly confirmed that more aromatic compounds detected when the roasting temperature increase. It is correlated with the discrimination result using electronic nose. The loading plot interpretation provides information that TGS822 and TGS826 are the most affecting sensors for discrimination of coffee aroma with varied roasting temperature. In the future, the electronic nose is potentially applied in coffee industry for quality control during process.